Display of Native SARS-CoV-2 Spike on Mammalian Cells to Measure Antibody Affinity and ADCC - Rebecca Wilen; Annalee Nguyen; Ahlam Qerqez; Jennifer Maynard (Bio-Protocol)
The COVID-19 pandemic led to the rapid development of antibody-based therapeutics and vaccines targeting the SARS-CoV-2 spike protein. Several antibodies have been instrumental in protecting vulnerable populations, but their utility was limited by the emergence of spike variants with diminished susceptibility to antibody binding and neutralization. Moreover, these spike variants exhibited reduced neutralization by polyclonal antibodies in vaccinated individuals. Accordingly, the characterization of antibody binding to spike variants is critical to define antibody potency and understand the impact of amino acid changes. A key challenge in this effort is poor spike stability, with most current methods assessing antibody binding using individual domains instead of the intact spike or variants with stabilizing amino acid changes in the ectodomain (e.g., 2P or HexaPro). The use of non-native spike may not accurately predict antibody binding if changes lie within the epitope or alter epitope accessibility by altering spike dynamics. Here, we present methods to characterize antibody affinity for and activity against unmodified SARS-CoV-2 spike protein variants displayed on a mammalian cell membrane that recapitulates the native spike environment on infected cells. These include a flow cytometry–based method to determine the effective antibody binding affinity (KD) and an antibody-dependent cellular cytotoxicity (ADCC) assay to assess Fc-mediated activities. These methods can readily evaluate antibody activity across a panel of spike variants and contribute to our understanding of spike/antibody co-evolution.